The Buzzer Phenomenon and Legal Protection for Businesses Related to Negative Reviews on Social Media - Ulima Bahtiar Pratiwi; Mutimatun Niami (Proceeding International Conference Restructuring and Transforming Law, 2025)
The development of information technology and the advancement of social media platforms in recent years have changed the way businesses and consumers communicate. Social media allows businesses to promote their products, but also presents challenges related to negative reviews from consumers and third parties, such as buzzers and food vloggers. Negative reviews from buzzers are often detrimental to businesses’ reputation, while food vloggers who give harsh reviews have the potential to reduce turnover and business image. However, constructive reviews can be beneficial for business quality improvement. In Indonesia, the Electronic Information and Transaction (ITE) Law provides a legal basis for the dissemination of harmful information, but the line between freedom of expression and legal protection for businesses remains problematic. This research aims to explore the mechanism of employers' legal umbrella regarding negative reviews, with the process of analyzing existing laws and regulations and comparing positive reviews from well-known reviewers and negative reviews from buzzers or food vloggers. The research uses a qualitative approach and normative method, collecting data through literature study, document analysis, and case studies. The results show the need for clearer regulations regarding the limits of reviews, as well as the importance of the principles of good faith and honesty in providing reviews on social media. Preventive and repressive legal protection can be applied to protect businesses from unfair negative reviews, taking into account aspects of freedom of expression guaranteed by law.